Selecting and tuning a temperature feedback controller for water heating process. - Yap, Kristian July R. (UPCOE NEC Technical Bulletin)
Temperature control is necessary for temperature-specific industrial operations in order to meet optimum operating conditions based on the desired product specifications. In line with this, an experiment on temperature control was conducted to select an appropriate feedback controller and determine its tuning parameters. A first order plus dead time (FOPDT) model was employed to characterize the system. Tuning parameters were determined through computer simulation using SciLab (version 5.0.3) by trial-and-error. Results show that upon using a PI controller with Kc=30.00 and Ki=0.71, a temperature deviation of about 2°C for the half pail set-up and a 10-minute settling time deviation for the full pail set-up occurred. This was due to several factors such as the ideality and absence of mixing in the mathematical model, and the difference in the conditions of the environment. Though a PID controller was theoretically used, a PI-controlled system was found to be more suitable.